Nonionic Mixed Surfactant Stabilized Water-in-Oil Microemulsions for Active Ingredient In Vitro Sustained Release - Yew, H.C.; Misran, M. (Wiley, 2016)
Olive oil is an excellent dispersing medium for water-in-oil microemulsions as it helps hydrate the skin and enhances the release of the active ingredients. In this study, mixed surfactants containing Span® 80 with varied Tween® series at 1:1 ratio were prepared with olive oil and water to produce water-in-oil microemulsions. The microemulsions were used to study the in vitro release of the active ingredients with different water solubilities. A microemulsion olive oil/water/mixed surfactant (56:4:40 by weight) was selected from the constructed phase diagram for further physical characterization. The analysis showed that the microemulsion composed of Span® 80 and Tween® 80 (ST80) was the most suitable surfactant combination. Equal amounts of ascorbic acid, caffeine and lidocaine were solubilized in ST80 microemulsions to study their release rate. Physical evaluation of ST80 microemulsions incorporating the active ingredients showed no apparent change compared to the ST80 microemulsion alone. The in vitro release study showed that the rate of active ingredients released from the microemulsion into the receptor chamber depends on their hydrophobicity, whereby lidocaine and caffeine were fivefold and twice as fast, respectively, with respect to ascorbic acid. ST80 microemulsions show constant rate of active ingredient release, demonstrating the sustained release properties of the system.